PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA DALAM PENYEBARAN FOTO DAN VIDEO ASUSILA MELALUI MEDIA SOSIAL(Studi Putusan Nomor: 429/Pid.Sus/2022/PNTjk) - Opan Saputra; I Ketut Seregig; Yulia Hesti (JOURNAL OF LAW AND NATION, 2024)
Immoral crime is an act that deviates from the norms of decency which describes the actions and views of the harasser to the person being harassed where the views are humiliating,demeaning or worthless. Research problems regarding the criminal causes of theperpetrators of spreading immoral photos/videos through social media and the criminalresponsibility of the perpetrators of spreading immoral photos/videos through social media.The research method uses: 1. a normative juridical approach carried out by studying normsor rules, 2. an empirical approach carried out by interviewing informants. The causativefactor was that it was true that the perpetrator did not accept it because the witness-victim wanted to end his romantic relationship with the perpetrator, so without the permission andknowledge of the witness-victim, the perpetrator spread the immoral pictures/photos/videosof the witness-victim. Criminal responsibility for the perpetrator has fulfilled all the elementsin accordance with the indictment by the public prosecutor with an alternative form ofindictment to Article 27 paragraph (1) of the ITE Law, so the Judge imposes a sentence onthe perpetrator with imprisonment for 3 (three) years and a fine of IDR 1 ,000,000,000.00(one billion rupiah) if the fine is not paid then it is replaced by imprisonment for 4 (four)months. The judge's decision is appropriate and ensnares the perpetrator so that he does notrepeat his actions in the future, and creates a deterrent effect on the perpetrator.